Anxiety disorders in mothers and their children: Prospective longitudinal community study - Andrea Schreier; Hans‐Ulrich Wïttchen; Michael Höfler; Roselind Lieb (2008)
Summary The relationship between DSM-IV anxiety disorders and their clinical characteristics in mothers and anxiety in offspring was examined in 933 mother–child pairs from a longitudinal community study. Offspring of mothers with an anxiety disorder had an elevated risk of developing any anxiety disorder, compared with offspring of mothers with no anxiety disorder. Increased risk of anxiety in the offspring was especially associated with maternal social phobia and generalised anxiety disorder, and with maternal diagnoses of early onset, greater number and more severe impairment. These results suggest that the type of maternal anxiety disorder and its severity of manifestation contribute to mother-offspring aggregation of anxiety.